Certification by the American Board of Surgery among U.S. Medical Graduates - Andriole, Dorothy A. (2012)
BACKGROUND: We sought to identify variables associated with American Board of Medical Specialties (ABMS)-member-board certification and lack thereof among U.S. medical graduates who planned at medical-school graduation to become certified in surgery and entered graduate medical education (GME) in general surgery. STUDY DESIGN: De-identified, individualized records updated through March 2009 for all 1993–2000 U.S. medical school matriculants who graduated by 2002, intended to become certified in surgery, and entered general surgery training were analyzed using multivariable logistic regression to identify variables associated with graduates’ board certification status, including American Board of Surgery (ABS)-board certified (BC), other ABMS-member-BC (other-BC) and non-BC. RESULTS: Of 3373 graduates included in the study sample, 2036 (60.4 %) were ABS-BC, 342 (10.1 %) were other-BC, and 995 (29.5 %) were non-BC. Graduates who were women, > 26 years old at graduation, and initially failed United States Medical Licensing Examination (USMLE) Step 2 Clinical Knowledge (2CK) were more likely, and graduates who rated the quality of their surgery clerkship in medical school more highly were less likely, to be other-BC vs. ABS-BC. Graduates who were women, underrepresented minority race/ethnicity, Asian/Pacific Islander race/ethnicity, > 28 years old at graduation, initially failed USMLE Step 1, initially failed or received low passing scores on USMLE Step 2CK and graduated in more recent years were more likely to be non-BC vs. ABS-BC. CONCLUSIONS: Demographic and professional development variables were associated with ABMS-member-board certification status among U.S. medical graduates who had intended at medical-school graduation to become certified in surgery.